STATIC ANALYSIS OF FUNCTIONALLY GRADED (FGM) COMPOSITE PLATES - Öktem, Ahmet Sinan (Gazi Univ, Fac Engineering Architecture, 2014)
Static analysis of functionally graded (FGM) plates based on a higher order shear deformation theory is performed using an analytical solution technique. The boundary-discontinuous double Fourier series approach is used to solve a system of highly coupled linear partial differential equations with the mixed type clamped and simply supported boundary conditions prescribed at the edges. The mechanical properties of the plate are assumed to vary in the thickness direction according to a power-law distribution in terms of the volume fractions of the constituents. Analytical results are compared with finite element counterparts using commercially available software under uniformly distributed load. Present results are in good agreement with the finite element counterparts.
Keywords: Functionally graded composite; static analysis; analytical solution; Fourier method